UTILIZATION OF INFORMATION TECHNOLOGY IN ATTRACTING PUBLIC INTEREST IN MADRASAH - Istianah Masruroh Kobandaha; Burhanudin Abdul Karim Mantau (Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
This article is the result of research that aims to find out how to use information technology in attracting public interest in Madrasahs. This research is categorized as a qualitative research. Sources of data obtained through observation techniques, interviews, and documentation. The results of this study indicate that the use of Information Technology in Madrasah Aliyah Negeri Kotamobagu, in attracting public interest, has been carried out and continues to be developed, so that it has a very positive impact on institutions in publishing and attracting public interest. This study also found that public interest in the State Madrasah Aliyah Kotamobagu shows a very significant development every year, especially after being supported by facilities and infrastructure that further improve the quality of the institution, so that currently the Madrasah Aliyah Negeri Kotamobagu is a priority and the main choice for the community, and the public's view so far that Madrasah is identical with a slum institution will slowly turn into a quality modern institution.